Child Marriage And Its Impact in Indonesia in 2021 - Rahayu, Astuti (AIBPM Publisher, 2022)
One of the development problems that still occurs in Indonesia is the high number of child marriages. From the average figure of 9.23 percent in 2021, it still has to be lowered to achieve the target of 8.74 percent in 2024. This paper aims to look at the number of child marriages per province in Indonesia, because of the impact on child labor, not completing school, as well as policy implications. The results obtained from the literature study show that in 2021 there are 22 provinces that have child marriage rates above the national average. There are even 5 provinces that have increased from 2020. The causes of child marriage are multi-dimensional. Estimates using provincial cross-sectional data show that child marriage in Indonesia has a significant positive influence on child labor rates, on the level of not completed Junior High School education, and level of not completed Senior High School education. It takes a concerted effort from all parties so that the number of child marriages can be reduced significantly.